(untitled) - Hiroyuki, Suzuki (Tokyo, 2018)
Securing the generous support of the politicians and industrialists who propelled Japan's modernization, Ogawa Jihei VII created many outstanding gardens at the end of the nineteenth and the first few decades of the twentieth century. Expressing a Japanese aesthetic even while incorporating modern techniques, his methodology reveals the nature of modernization as Japan experienced it. With a keen eye for architecture, the author takes a long-awaited look at modernization and the modern garden
Keywords: Vườn,Gardens; Lịch sử,History; Nhật Bản,Japan